Predicted versus measured thoracic gas volumes of collegiate athletes made by the BOD POD air displacement plethysmography system - Wagner, D. R. (Applied Physiology, Nutrition, and Metabolism, 2015)
Measured (TGVm) and predicted (TGVp) thoracic gas volumes from the BOD POD were compared in 33 lean, university athletes. On average, TGVp (3.529 L) was not significantly different (p = 0.343) from TGVm (3.628 L); however, there was a bias (r = -0.703, p < 0.001). The difference in the percentage of body fat (BF) was within ±2% BF for 76% of the sample, but athletes at the extremes of height should have TGV measured.